An ethnography of caste and class at an Indian university: creating capital. Issue 3 (3rd July 2018) - Pathania, Gaurav J.; Tierney, William G.
Abstract: Despite having outlawed the caste system and the concept of untouchability in 1947, caste identity remains a cornerstone of social, political and economic life in India. Like other social institutions, educational institutions are the reflection of caste prejudices and discrimination. The recent inclusion of lower castes through the reservation system (affirmative action) has changed the nature of higher education. Based on an ethnographic account of a university campus and students' perceptions about caste issues, the authors suggest that the structure of higher education in India is designed in a manner that exacerbates, instead of ameliorates, tensions of class and caste. Using Bourdieu's notion of cultural capital, the paper defines the existing campus culture as a 'caste culture'. The text concludes that elite institutions do not yet guarantee the capability to overcome existing caste prejudices and stereotypes, regardless of structural attempts at reform.